Recent progress in hormone research : the proceedings of the Laurentian Hormone Conference. - Pincus, Gregory, 1903-1967 (Academic Press, Inc., Publishers, 1948)
Recent Progress in Hormone Research, Volume III contains papers delivered at the 1947 Laurentian Hormone Conference. This volume is organized into five parts encompassing 12 chapters that cover growth, metabolic, and steroid hormones. The opening parts cover the biochemical and physiological aspects of growth, metabolic, and steroid hormones. These parts particularly review the functions of the so-called sexogens, as well as some diseases caused by steroids, such as the Addison's disease. The succeeding parts describe the methods adaptable to the study of metabolic hormone problems. The remai.